The connotations of Quranic words and their effects on societal cohesion - Mansur, Inst. Dr. Israa Muhammed Mansur; Hussain, Assist. Prof. Dr. Husaain Kadhum Hussain (Sulaimani Journal for Humanities, 2026)
The Holy Quran has used words with great care in the formulation appropriate to the context in which they performed. In the Arabic language, and in addition to the Holy Quran, there are refined rhetorical and educational methods for raising children in a righteous manner, far from the filth of sins and the burdens of transgressions prevalent in our society and present-day Islamic societies. These methods depict events for us in a captivating artistic and aesthetic image that hearts submit to and minds and intellects listen to in a vivid and present image. It does not explicitly state the crime in the contexts of the Holy Quran, but we see it allude to it, and hint at it with words that dispense with explicitness due to the richness and richness of the words of the Arabic language. The Holy Quran has taken into account the social bonds between members of the same family, and strengthened their construction and warned against dismantling them, even if they were greatly different, especially in religious beliefs. This difference and disparity did not prevent that life from continuing, but it is marred by some major, decisive events that separate its bonds and sever the connection between them. The bond of fatherhood remains between the father and his son, and the bond of brotherhood remains even if it is afflicted by what It has been affected by a transgression of societal boundaries, norms and traditions. The Qur’an has been very careful to ensure that these relationships are strong and lasting.
Keywords: implications of words; Quranic words; societal cohesion